Auditoría de cumplimiento y presupuesto de resultados del distrito de Capelo 2024 - Bardalez Villacorta, Jorge (2025)
This basic, quantitative, correlational study with a non-experimental and cross sectional design, which included 40 subordinates as a population, was carried out with the objective of determining how the compliance audit influences the results budget of the Capelo District 2024. To do so, the survey and questionnaire were used to collect the required data. According to the results of the total number of respondents, 5.0% responded that they almost never carry out compliance audits, 12.5% stated that they do so sometimes, and 15.0% stated that they never carry them out. On the other hand, 30.0% indicated that they almost always carry out these audits, while 37.5% stated that they always carry them out. On the other hand, 2.5% indicated that they almost never have a results budget, 15.0% indicated that they sometimes have one, and another 15.0% stated that they never have one. On the other hand, 30.0% responded that they almost always have this budget, while 37.5% stated that they always have a results-based budget. In addition, a significance value (observed critical value) of 0.000 < 0.05 was found. We reject the null hypothesis and accept the alternative hypothesis. In conclusion, the compliance audit positively influences the results budget of the Capelo District.